Effect of tillage, residue and nitrogen management on yield, water and nitrogen use efficiency of wheat (Triticum aestivum) - BANDYOPADHYAY, K K; BHATTACHARYA, PRIYA; KRISHNAN, P; MAITY, P P; PURAKAYASTHA, T J; BHATIA, A; CHAKRABARTI, B; ADAK, SUJAN (The Indian Journal of Agricultural Sciences, 2023)
A two-year field study was carried out during winter (rabi) seasons of 2020–21 and 2021–22 at the research farm of ICAR-Indian Agricultural Research Institute, New Delhi with the aim of examining the impacts of various methods of tillage, residue management and nitrogen (N) application on wheat (Triticum aestivum L.) yield, water use efficiency (WUE), and nitrogen use efficiency in terms of Partial Factor Productivity of Nitrogen (PFPN). The study utilized a split-split plot design with 3 replications, where the main plot consisted of two tillage systems [conventional tillage (CT) and no tillage (NT)], the subplot comprised 2 residue levels [maize residue @5 t/ ha (R+) and no residue (R0)], and the sub-sub plot involved 3 N levels [60, 120, and 180 kg N/ha, representing 50% (N60 kg N/ha), 100% (N120 kg N/ha), and 150% (N180 kg N/ha)] respectively. The results indicated that both tillage and residue management considerably influenced the grain and biomass yield of wheat. Over the two years, NT exhibited a 7% higher WUE compared to CT, but the change was insignificant. However, in years with lower rainfall, crop residue mulching had a significant positive impact on WUE, while in years with higher rainfall; its effect on WUE was insignificant. Moreover, tillage practices had a considerable effect on the PFPN. In the year 2020–21, PFPN under NT was 3.59% higher than under CT, and in the year 2021–22, it was 2.06% higher. Furthermore, with an increase in N levels, WUE showed a substantial increase, while PFPN decreased.